1995
DOI: 10.1088/0953-4075/28/24/016
|View full text |Cite
|
Sign up to set email alerts
|

Low and intermediate energy coplanar symmetric (e, 2e) cross sections for the ionization of neon

Abstract: Triple-differential cross sections (TDCS) are measured in a coplanar symmetric energy sharing geometry for a neon target. The experiments were carried out for ionization of the 2p orbital between 500 and 65 eV incident energy and of the 2s orbital at 226.9 and 126.9 eV incident energy. The main difference compared to helium target is the apparition of a structure at 85 degrees for ionization from both orbitals. This structure, clearly seen at 65 eV for the 2p shell, is enhanced as the incident energy decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…All results are normalized to unity at ξ = 45 • . draw comparisons between the influence of the recoil peak for the 1π u orbital of N 2 and that of the atomic 2p 6 orbital of neon (Rosel et al 1991, Rioual et al 1995. A similar comparison can also be made for the results presented here at 36.7 eV with those for the 2p 6 orbital of neon at 41.6 eV (Murray and Read 2000), where the cross-section is observed to have a similar shape.…”
Section: Resultssupporting
confidence: 65%
“…All results are normalized to unity at ξ = 45 • . draw comparisons between the influence of the recoil peak for the 1π u orbital of N 2 and that of the atomic 2p 6 orbital of neon (Rosel et al 1991, Rioual et al 1995. A similar comparison can also be made for the results presented here at 36.7 eV with those for the 2p 6 orbital of neon at 41.6 eV (Murray and Read 2000), where the cross-section is observed to have a similar shape.…”
Section: Resultssupporting
confidence: 65%
“…Besides the variation trends for the forward and backward scattering peaks, at incident energies of 35 These similar bumps were also observed in the TDCS for s valence orbitals of Mg [15], K [15], Ca [15], Ne [35], Ar [36], and Kr [37], but not observed in He [38,39]. Considering the similarities and differences in electronic structures of these atoms, we calculated the TDCS of Na by switching off the interaction between active electron and passive s or p electrons from the distorting potentials.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity and position of the forward and backward peaks have been widely studied for He, Ne, Ar, Kr, H, alkali, and alkali earth atoms. [1−11] In addition to forward and backward peaks, a new structure in the TDCS of Ne has been found by Rioualt et al [4] They reported their experimental and theoretical (e, 2e) research and found a new struc-ture at a symmetric scattering angle of 85 • . They ascribe the structure to the fact that the outgoing electrons experience an elastic scattering with the target ion by 90 • , followed by a direct collision.…”
Section: Introductionmentioning
confidence: 92%